2015
DOI: 10.1111/jcpe.12326
|View full text |Cite
|
Sign up to set email alerts
|

Impaired neutrophil directional chemotactic accuracy in chronic periodontitis patients

Abstract: AimTo investigate the chemotactic accuracy of peripheral blood neutrophils from patients with chronic periodontitis compared with matched healthy controls, before and after non-surgical periodontal therapy.Material & MethodsNeutrophils were isolated from patients and controls (n = 18) by density centrifugation. Using the Insall chamber and video microscopy, neutrophils were analysed for directional chemotaxis towards N-formyl-methionyl-leucyl-phenylalanine [fMLP (10 nM), or CXCL8 (200 ng/ml)]. Circular statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 73 publications
3
61
2
Order By: Relevance
“…Neutrophils are the predominant immune cell in periodontitis (18), and the results presented here support the suggestion that their stimulation with periodontal bacteria promotes extracellular, intracellular, and superoxide ROS release; however, data indicate that this may be species specific. Indeed, some species consistently elicited higher levels of neutrophil ROS production, while other bacteria, such as P. gingivalis or S. sanguinis, were not found to significantly promote ROS release.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…Neutrophils are the predominant immune cell in periodontitis (18), and the results presented here support the suggestion that their stimulation with periodontal bacteria promotes extracellular, intracellular, and superoxide ROS release; however, data indicate that this may be species specific. Indeed, some species consistently elicited higher levels of neutrophil ROS production, while other bacteria, such as P. gingivalis or S. sanguinis, were not found to significantly promote ROS release.…”
Section: Discussioncontrasting
confidence: 43%
“…It has also been reported that neutrophil chemotaxis is compromised in patients with chronic periodontitis and that these patients' neutrophils produce the chemoattractant interleukin-8 in excess when stimulated, potentially creating distracted chemotaxis (31). Such processes may increase neutrophil tissue transit times and thereby potentially exacerbate ROS-mediated collateral tissue damage (18).…”
Section: Figmentioning
confidence: 99%
“…Neutrophil migration toward sites of infection is a key early event in the process of protection against pathogenic microorganisms, and in peri-odontal disease, neutrophils are recruited in high numbers into the gingival tissues and crevicular fluid to control and combat the bacterial infection (35). However, neutrophils from chronic periodontitis patients show dysfunctional chemotactic function which increases the cell transit time in the gingival connective tissue, promoting collateral tissue damage (36). Using a mouse chamber model, we recently showed that F. alocis infection resulted in rapid neutrophil infiltration to the site of infection (10).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies from our group have shown that neutrophils from periodontitis patients are hyper-reactive and contribute to tissue destruction [3,19,20] . These neutrophils have also been shown to present a cytokine hyper-reactivity [21] and a dysfunctional chemotaxis [22] . When the resolution of inflammation is not achieved, antigen-presenting cells are activated by bacterial pro-ducts and interact with naïve T helper cells (Th0), driving their differentiation into several subsets, such as Th1, Th2, Th17, and Treg.…”
Section: Periodontal Diseasementioning
confidence: 99%